Dancing and prompting, etiquette and deportment of society and ball room. - Bonstein (Professor) (Boston, White, Smith & Co., 1884)
Assembled by Professor Bonstein (pseudonym for Charles A. White) from the writings of others, this manual begins with advice to parents regarding children: "Send them to dancing school and save many a doctor's bill." The etiquette section in this manual is reduced to a section simply called "hints." The author provides advice to prompters and rules for calling quadrilles. Of the many popular ballroom dances performed in the ballroom, only the quadrille, German (also known as the cotillon), and contra dances are discussed.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Etiquette; Dance Instruction and Technical Manuals; Prompting Quadrilles